1987 BUDGET (Tufts Archival Research Center, 2007)
Confidential; Memorandum of budget projections for 1987. Notes that the Tobacco Institute will be significantly over budget and provides recommendations for cost reduction and elimination. Cites fire fighter coalitions with the tobacco industry as a specific cause of over budgeting.